Features of coordination in primary school children - Марченко, С. І.; Бережняк, Б. А. (Physical Education Theory and Methodology, 2014)
Objective: to define the features of coordinating preparedness of pupils of primary school age. Methods and organization studies. The study used the following methods: method of theoretical analysis and synthesis of the literature, the study of documentary materials, teacher observation and timing of studies; method of control tests, pedagogical experiment, methods of mathematical statistics. In the experiment 60 students participated: 20 — 2 classes, 20 — 3 classes, 20 — 4 classes. Conclusions. In the primary school age girls are taller than boys, the level display of static balance and dynamic balance performance growth over boys girls. The obtained data the age of coordination abilities point to the need to develop methods differentiated physical education of children of primary school age. Children are not involved in sports and have a medium and low rates of physical fitness, is to focus on improving personal performance.